Copolímeros de anilina e amino derivados de m-tetrafenilporfirina - Pereira, Guilherme Miranda (2011)
Meso-tetraphenylpophyrins (H2TPP) derivatives have attracted great interest among scientists due their electronic properties, which can be used in molecular electronics, photocells, power storage among other things. In this work were synthesize rich aniline copolymers with a aminated derivative of H2TPP, the BATPP, to study the effects of porphyrin insertion in the electrical, electrochemical and photophysic properties. The BATPP was copolymerized with aniline in the proportion of 2,5% and 5,% in mol of aniline. The product was called PAni-BATPP2,5 and PAni-BATPP5. The copolymers were characterized by FTIR, UV-vis and fluorescence spectroscopy. The electrical conductivity (σ) of the copolymers decreased when the BATPP portion was increased. PAni showed σ of ca. 4,77 S/cm, while PAni-BATPP2,5 and PAni-BATPP5 showed 1,44 and 1,21 S/cm, respectively. This decrease can be related to the increase of "branches" of the final polymer, which is related to decreasing of the copolymer crystallinity. Cyclic voltammetry measurements displayed a decrease of the oxidation potentials of the copolymers in relation to pristine PAni, which corroborates with UVvis spectra. This decrease was assigned to an increase on the electronic density in the copolymers. Zinc ions were added to the copolymers to form a coordinate compound with the BATPP of the polymeric backbone. The zinc complexed copolymers also were characterized by FTIR, UV-vis and fluorescence spectroscopy. The photoactivity of the complexed copolymers and non-complexed ones were obtained by differential voltammetry (DV) measurements. Photocurrents curves, obtained by DV, showed no clearly relation among the samples, due to weak interaction among the samples and the FTO-glass. However, also was observed that photocurrent) increase as the proportion of BATPP increase in the copolymer, reaching the biggest values in the copolymers complexed with Zn2+. The higher photocurrent value was obtain for PAni-BATPP5Zn on the potential of 0,8 V. The obtaining of the copolymers suggest that BATPP is a susceptible monomer to oxidative polymerization with aniline e their derivatives, which enables to attach porphyrins in several other polymeric systems.